الأخطاء اللغوية فى التعبير الشفوي لدي طلاب لغير الناطقين بها في كاليمنتان الجنوبية - Oensyar, M. Kamil Ramma (UIN Maulana Malik Ibrahim Malang, 2024)
Speaking skill is a language ability in pronouncing articulation sounds or uttering words to express thoughts, opinions, and feelings to other people as speakers. Language errors are the use of speech forms of various linguistic units which include words, sentences, paragraphs, which deviate from the system of language rules. Many of the students from Darul Hijrah Islamic boarding School experienced language errors in using Arabic as their daily language. The purpose of this research is to find out the form of errors and factors that cause language errors in students' speaking skills. This research is a qualitative research using a descriptive analysis approach. Data collection techniques were carried out using observation, interviews, and documentation. The subjects of this study were old students and language supervisors at Darul Hijrah Islamic boarding School. Based on the results of the study, linguistic errors in daily conversations made by students of Islamic boarding School are divided into 7 forms of errors, namely errors in adding letters outside of Arabic, using repeated words, question words, the word